Investigation into the Impact and Buffering Characteristics of a Non-Newtonian Fluid Damper: Experiment and Simulation - Jingya Sun; Sujuan Jiao; Xiuchang Huang; Hongxing Hua (Shock and Vibration)
Dampers are widely applied to protect devices or human body from severe impact or harmful vibration circumstances. Considering that dampers with low velocity exponent have advantages in energy absorption, they have been widely used in antiseismic structures and shock buffering. Non-Newtonian fluid with strong shear-thinning effect is commonly adopted to achieve this goal. To obtain the damping mechanism and find convenient methods to design the nonlinear fluid damper, in this study, a hydraulic damper is filled with 500,000 cSt silicone oil to achieve a low velocity exponent. Drop hammer test is carried out to experimentally obtain its impact and buffering characteristics. Then a coupling model is built to analyze its damping mechanism, which consists of a model of impact system and a computational fluid dynamics (CFD) model. Results from the coupling model can be consistent with the experiment results. Simulation method can help design non-Newtonian fluid dampers more effectively.